Delving into the world of Turkish 9th grade EFL students in a flipped classroom context: Analyzing perceptions and experiences - Nermin Yıldız Yüksel; Gülşah Külekçi (Literacy Trek)
Flipped classroom, which combines online and face-to-face learning, is an innovative model. This study examined the 9th grade Turkish students' experiences learning English in a flipped classroom. Nineteen students from a high school in İzmir participated in the study. An intrinsic case study was employed as a qualitative research design to investigate the effectiveness of the flipped classroom from the viewpoint of 9th grade EFL students. Data were collected through student journals, teacher journals, and focus group interviews. The data collected was analyzed by using thematic analysis. The results showed that the flipped classroom model enhanced the students' language skills, especially in speaking, and encouraged active participation, motivation, and collaboration. Most of the students found the model more time-efficient compared to traditional classrooms. Furthermore, the students valued the flexibility of learning at their own pace but reported challenges such as adapting to the model, inadequate preparation, and internet connectivity issues.